Profiling of circulating tumor DNA in plasma of non‐small cell lung cancer patients, monitoring of epidermal growth factor receptor p.T790M mutated allelic fraction using beads, emulsion, amplification, and magnetics companion assay and evaluation in future application in mimicking circulating tumor cells. (21st May 2019) - Garcia, Jessica; Wozny, Anne‐Sophie; Geiguer, Florence; Delherme, Aurélia; Barthelemy, David; Merle, Patrick; Tissot, Claire; Jones, Frederick S.; Johnson, Chassidy; Xing, Xiaobin; Xu, Zhenyu; Edelstein, Daniel L.; et al.
Abstract: Cell‐free plasma DNA (cfDNA) and mimicking circulating tumor cells (mCTCs) have demonstrated tremendous potential for molecular diagnosis of cancer and have been rapidly implemented in specific settings. However, widespread clinical adoption still faces some obstacles. The purpose was to compare the performance of a BEAMing (beads, emulsion, amplification, and magnetics) assay (OncoBEAM™‐epidermal growth factor receptor [ EGFR ] [Sysmex Inostics]) and a next‐generation sequencing assay (NGS; 56G Oncology panel kit, Swift Bioscience) to detect the p.T790M EGFR mutation in cfDNA of non‐small cell lung cancer (NSCLC) patients. CfDNA samples (n = 183) were collected within our hospital from patients having a known EGFR sensitizing mutation, and presenting disease progression while under first‐line therapy. EGFR mutations were detected using NGS in 42.1% of samples during progression in cfDNA. Testing using the OncoBEAM™‐ EGFR assay enabled detection of the p.T790M EGFR mutation in 40/183 NSCLC patients (21.8%) versus 20/183 (10.9%), using the NGS assay. Samples that were only positive with the OncoBEAM™‐ EGFR assay had lower mutant allelic fractions (Mean = 0.1304%; SD ± 0.1463%). In addition, we investigated the detection of p.T790M in mCTCs using H1975 cells. These cells spiked into whole blood were enriched using the ClearCellFX1 microfluidic device . Using the OncoBEAM™‐ EGFR assay, p.T790M was detected in as few as 1.33 tumoral cells/mL. Overall, these findings highlight the value of using the OncoBEAM™‐ EGFR to optimize detection of the p.T790M mutation, as well as the complementary clinical value that each of the mutation detection assay offers: NGS enabled the detection of mutations in other oncogenes that may be relevant to secondary resistance mechanisms, whereas the OncoBEAM™‐ EGFR assay achieved higher sensitivity for detection of clinically actionable mutations. Abstract : In cell‐free DNA and mimicking circulating tumor cells (sensitivity at 1.33 tumoral cells/mL whole blood), for the first time, we highlighted the value of using the OncoBEAM TM ‐epidermal growth factor receptor ( EGFR ) to optimize detection of the p.T790M mutation, as well as the complementary clinical value that each of the mutation detection assay offers: next‐generation sequencing provided enhanced coverage of EGFR mutations, and enabled the detection of mutations in other oncogenes, whereas the OncoBEAM TM ‐ EGFR assay achieved higher sensitivity for detection of clinically actionable mutations such as p.T790M.